2013
DOI: 10.1111/ijcp.12308
|View full text |Cite
|
Sign up to set email alerts
|

Initial combination of linagliptin and metformin in patients with type 2 diabetes: efficacy and safety in a randomised, double‐blind 1‐year extension study

Abstract: ObjectiveTo determine the efficacy and safety of linagliptin in initial combination with metformin in patients with type 2 diabetes.MethodsThis 1-year randomised, double-blind study was an extension of a 6-month randomised controlled trial, in which adults with type 2 diabetes received one of six treatment regimens (linagliptin 2.5 mg plus metformin 500 mg bid, linagliptin 2.5 mg plus metformin mg 1000 bid, metformin 1000 mg bid, metformin 500 mg bid, linagliptin 5 mg qd or placebo). In the extension, patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“… 26 Further evidence of the efficacy of this combination was provided by a 52-week study demonstrating that initial combination therapy with linagliptin and metformin was superior to metformin monotherapy for reducing HbA1c levels in patients with poor glycemic control, with the additional benefits of no weight gain and a low risk of hypoglycemia. 27 …”
Section: Discussionmentioning
confidence: 99%
“… 26 Further evidence of the efficacy of this combination was provided by a 52-week study demonstrating that initial combination therapy with linagliptin and metformin was superior to metformin monotherapy for reducing HbA1c levels in patients with poor glycemic control, with the additional benefits of no weight gain and a low risk of hypoglycemia. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Notably, only 14 of 31 patients with baseline HbA 1c levels ≥9% remained in the metformin monotherapy group at the end of the extension trial ( Table 2 ). 9 …”
Section: Clinical Evaluation Of Linagliptin/metformin Lpcmentioning
confidence: 99%
“…Not surprisingly, results from several studies have shown that initial combination therapy with metformin and a DPP-4 inhibitor provides greater improvement in glycemic control than monotherapy with either agent [14,[18][19][20]. For example, results from a 24-week study with linagliptin plus metformin demonstrated greater placebo-corrected reductions in HbA1c with initial combination therapy than monotherapy with either component: -1.7% for linagliptin 5 mg/metformin 2000 mg, -1.3% for linagliptin 5 mg/metformin 1000 mg, -1.2% for metformin 2000 mg, -0.8% for metformin 1000 mg, and -0.6% for linagliptin 5 mg (all p \ 0.0001) [18].…”
Section: Efficacy Considerations With a Combination Of Metformin And mentioning
confidence: 99%